2007
DOI: 10.1016/j.critrevonc.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of erythropoietin in the brain

Abstract: Multi-tissue erythropoietin receptor (EPO-R) expression provides for erythropoietin (EPO) activity beyond its known regulation of red blood cell production. This review highlights the role of EPO and EPO-R in brain development and neuroprotection. EPO-R brain expression includes neural progenitor cells (NPC), neurons, glial cells and endothelial cells. EPO is produced in brain in a hypoxia sensitive manner, stimulates NPC proliferation and differentiation, and neuron survival, and contributes to ischemic preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
164
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(177 citation statements)
references
References 121 publications
3
164
0
10
Order By: Relevance
“…22 NF-kB activation during nerve injury can upregulate some downstream antiapoptotic and neuroprotective genes. 25,26 Digicaylioglu and Lipton 25 have reported that neuronal EPO-receptors activated the neuroprotective signalling pathway via Janus Kinase-2 (JAK2), and NF-kB. Liu et al 27 have observed a modest activation of NF-kB in rhEPO group before ischemia-reperfusion in myocardium and contributed this to the protective effects of rhEPO pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…22 NF-kB activation during nerve injury can upregulate some downstream antiapoptotic and neuroprotective genes. 25,26 Digicaylioglu and Lipton 25 have reported that neuronal EPO-receptors activated the neuroprotective signalling pathway via Janus Kinase-2 (JAK2), and NF-kB. Liu et al 27 have observed a modest activation of NF-kB in rhEPO group before ischemia-reperfusion in myocardium and contributed this to the protective effects of rhEPO pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…44 Epo, generally considered an erythropoietic growth factor, is also a potent prosurvival factor that protects developing stem and progenitor cells in a variety of organs. 45 Renal Epo gene expression differs between SIRT1 ϩ/Ϫ and SIRT1 ϩ/ϩ mice exposed to 6% O 2 , while both groups of mice have similar amounts of renal Epo mRNA under ambient O 2 . 44 Similarly, our data showed that hematopoietic progenitor colony formation from adult mice significantly differed between SIRT1 ϩ/ϩ and SIRT1 ϩ/Ϫ mice under 5% O 2 , while both groups of mice had similar numbers under normoxia.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Expression of EPO and its receptors in the nervous system, as well as its multifaceted protective actions in cell culture and animal models (e.g., induction of anti-apoptotic, anti-oxidant and anti-inflammatory signaling in neurons, glial and cerebrovascular endothelial cells, stimulation of angiogenesis, and neurogenesis), have been reported extensively and reviewed in detail elsewhere. [7][8][9][10][11][12][13][14][15][16][17] Therefore, this review will focus on 1) preclinical work published on EPO variants and 2) clinical studies in neuropsychiatric disease performed with EPO.…”
Section: Introductionmentioning
confidence: 99%